PENGARUH MODEL PEMBELAJARAN RQA (READING, QUESTIONING, AND ANSWERING) YANG DILAKSANAKAN SECARA DARING (MASA PANDEMI COVID-19) TERHADAP PENINGKATAN SELF REGULATED LEARNING DAN HASIL BELAJAR SISWA - Lisa, Defiana; Dewi, Nova Christina; Sahrin, Alvi (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
In distance learing or online, interesting learning innovations are needed to improve self-learning skills for students. The RQA (Reading, Questioning, And Answering) learning model is teaching oriented learning self-learning skills for students. This study aims to analyze the influence of learning models RQA on enhancement self regulated learning and learning result of student on the subject of  Matriks class XI SMA Negeri 1 Batang Angkola. The quasi experimenttal study used a design “nonquevalent control group design”. The sample of this research is student of class XI MIA 1 as experimental class with RQA model and XI MIA 4 as control class with conventional learning. In the research, technique of collecting data using test and questionnaire. Data analysis with Manova, using the app SPSS 21 for Windows. The result of the research analysis of the questionnaire indicated that the significance value of 0,000 < 0,05 which means that there is an influence of  RQA model on enhancement self regulated learning of student class XI SMA Negeri 1 Batang Angkola. Than, the result of the research analysis of test score indicated that the significance value of 0,000 < 0,05 which means that there is an influence of  RQA model on enhancement learning result of  student class XI SMA Negeri 1 Batang Angkola.